2020
DOI: 10.3390/ijms21030969
|View full text |Cite
|
Sign up to set email alerts
|

Precision Psychiatry Applications with Pharmacogenomics: Artificial Intelligence and Machine Learning Approaches

Abstract: A growing body of evidence now suggests that precision psychiatry, an interdisciplinary field of psychiatry, precision medicine, and pharmacogenomics, serves as an indispensable foundation of medical practices by offering the accurate medication with the accurate dose at the accurate time to patients with psychiatric disorders. In light of the latest advancements in artificial intelligence and machine learning techniques, numerous biomarkers and genetic loci associated with psychiatric diseases and relevant tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 76 publications
0
58
0
1
Order By: Relevance
“…On the other hand, it has been reported that married patients with MDD responded better to antidepressants as compared to unmarried ones [ 18 ]. Possible explanations for the discrepancies regarding marital status may be due to inadequate sample sizes, distinct study designs, diverse populations, and various confounding effects [ 1 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, it has been reported that married patients with MDD responded better to antidepressants as compared to unmarried ones [ 18 ]. Possible explanations for the discrepancies regarding marital status may be due to inadequate sample sizes, distinct study designs, diverse populations, and various confounding effects [ 1 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays researchers have been making significant progress in the interdisciplinary fields of pharmacogenomics, machine learning, and psychiatry [ 1 , 2 , 3 ]. In the arena of pharmacogenomics, the goal of machine learning research is to provide predictive algorithms that can in general help facilitate the investigation of how genetic variants and clinical variables can influence an individual’s treatment outcomes to drugs [ 1 , 2 , 3 ]. Latest advancements in machine learning algorithms have demonstrated their promising potentials with respect to pharmacogenomics for patients with psychiatric disorders [ 1 , 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the heterogeneity and complexity of MDD, single domain approaches just implementing one kind of parameter were of limited success [81]. Therefore, in the recent years, the field of personalized medicine and precision psychiatry proceeded to the application of artifical intelligence and machine-learning models [82,83] combining multi-variate data sets [75], and implementing biological and clinical patient profiles [84] in order to predict treatment outcome for psychiatric disorders in general, and MDD in particular.…”
Section: Exploring Predictors Of Treatment Responsementioning
confidence: 99%
“…Pharmacogenomics, a study of genomic influence in an individual's response to drug, highlights inter-individual differences in drug response and contributes to developing precision medicine; a customized treatment decision tailored for an individual based on his/her genetic profile [115]. In psychiatry, the current practice in line with this idea includes repurposing drugs via off-label prescribing [116].…”
Section: Drug Repurposing and Precision Medicinementioning
confidence: 99%